2014
DOI: 10.1016/j.ccr.2014.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Drugging MYCN through an Allosteric Transition in Aurora Kinase A

Abstract: Summary MYC proteins are major drivers of cancer, yet are considered undruggable, as their DNA binding domains are composed of two extended alpha helices with no apparent surfaces for small molecule binding. Proteolytic degradation of MYCN protein is regulated in part by a kinase-independent function of Aurora A. We describe a class of inhibitors that disrupts the native conformation of Aurora A, and drives degradation of MYCN protein across MYCN-driven cancers. Comparison of co-crystal structures with structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
245
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(259 citation statements)
references
References 48 publications
(60 reference statements)
14
245
0
Order By: Relevance
“…[12][13][14] Additional lines of evidence support further evaluation of Aurora A kinase inhibition in neuroblastoma. Increased expression of Aurora A kinase correlates with inferior outcomes in neuroblastoma.…”
Section: Introductionmentioning
confidence: 80%
“…[12][13][14] Additional lines of evidence support further evaluation of Aurora A kinase inhibition in neuroblastoma. Increased expression of Aurora A kinase correlates with inferior outcomes in neuroblastoma.…”
Section: Introductionmentioning
confidence: 80%
“…Interest in Aurora A and its conformational plasticity has recently increased owing to the discovery that inhibiting Aurora A with MLN8054 or CD532, both observed to bind Aurora A in an inactive T‐loop conformation, disrupts the interaction of Aurora A with the proto‐oncogenic transcription factor N ‐Myc. This leads to degradation of N ‐Myc and offers an alternative therapeutic strategy for N ‐Myc‐driven tumors (currently under clinical evaluation with MLN8237/alisertib) 5d, 6. These factors make Aurora A an excellent clinically relevant system for studying the heterogeneity and dynamics of T‐loop conformation underlying the observed structural and catalytic properties of protein kinases.…”
mentioning
confidence: 99%
“…MLN8054 and CD532 are both nanomolar inhibitors of Aurora A, and X‐ray structures show that each binds in an inactive T‐loop conformation (Figure S1 c, d) 5b,5d,5g. Although both are referred to as type II inhibitors, neither extends into the allosteric hydrophobic pocket, and neither has been captured binding the kinase with a canonical DFG‐out motif.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, MYCN is a transcription factors that was considered a poor drug target, until recent approaches suggested that down-regulation of MYCN could be possible by indirect targeting using Aurora kinase inhibitors or BET inhibitors. These concepts were proven using preclinical models [2][3][4][5][6] and are now entering clinical trials. …”
mentioning
confidence: 99%